2002
DOI: 10.1007/s00542-002-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Requirements of an industrially applicable microcutting process for steel micro-structures

Abstract: Micro-cutting offers good potentialities in order to manufacture small and medium lot sizes of micro-parts with arbitrary geometry at an economically reasonable expense. Either by direct machining or as a means to fabricate moulds for micro injection moulding, the major advantages turn out to be large removal rates, good compliance with tolerance ranges, high surface quality and a wide choice of materials which can be processed. Particularly if highly wear resistant materials are to be processes, as it is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…When micromachining inhomogeneous multi-phase material of different hardness and ductility for instance consisting of ferrite and pearlite, different ratios of cutting radius to grain size and varying phase ductility, imply that process mechanisms will differ [12,23]. Thus, Schmidt et al [23] preferred micromachining of finest and equidistantly distributed carbides steels or harder materials [12,22,23]. It can be concluded that to achieve a good surface finish for micromachining of steel with tungsten carbide tool, hard homogeneous material is the ideal choice [12,20].…”
Section: Quality Of Machined Surfacementioning
confidence: 99%
“…When micromachining inhomogeneous multi-phase material of different hardness and ductility for instance consisting of ferrite and pearlite, different ratios of cutting radius to grain size and varying phase ductility, imply that process mechanisms will differ [12,23]. Thus, Schmidt et al [23] preferred micromachining of finest and equidistantly distributed carbides steels or harder materials [12,22,23]. It can be concluded that to achieve a good surface finish for micromachining of steel with tungsten carbide tool, hard homogeneous material is the ideal choice [12,20].…”
Section: Quality Of Machined Surfacementioning
confidence: 99%
“…Precise control of the axis of a micromachine, with positioning error of less than 1 µm, is necessary to obtain micron-range machining dimensions [19]. Hence, the step cutting process of the microrod requires bespoke lines of numerical control (NC) codes that are not available in the usual computer-aided manufacturing (CAM) software.…”
Section: Cnc Program Generation For Micromachiningmentioning
confidence: 99%
“…Schmidt et al [79] investigated the influence of material state on the surface quality in micro milling steels and suggested the material should be heat treated in finest and equidistant micro structure prior to cutting so as to achieve constant cutting conditions, resulting in reasonable surface quality. Popov et al [80] modified micro structures of Al 5083 workpieces by equal channel angular pressing (ECAP) to achieve more homogeneous material properties.…”
Section: Work Micro Structure Effectmentioning
confidence: 99%